Feudal and Financial Resources for the Retired Princes in the Mamluk Army (648-923 H /1250-1517 AD) - Alamayreh, Mohammad Abdullah (Journal of Humanities & Social Sciences, 2021)
This study investigates the economic resources for the retired princes in the Mamluk army which came in the form of either state that varied in its size and production according to different considerations or financial allocations (movable and immovable) varied in their values, the times of its distribution and the party that is responsible for the distribution. Through the investigation of the Mamluk documents and the autobiographies of the retired princes, it was found that the sponsorship of those princes after retirement was according to the Sultan’s view and according to his estimation. This sponsorship is seen as part of the generosity of the Sultan, thus there were no criteria on which these resources were granted, however, it is an indicator that shows how much attention was paid to the retired princes and the appreciation of their efforts during war and peace times. This is an important side in the military pension system of the Mamluks which features their army in comparison with other Islamic armies.